Penanggulangan Penyalahgunaan Narkoba di Kalangan Generasi Muda di Kota Pekanbaru (ARSY : Jurnal Aplikasi Riset kepada Masyarakat, 2025)
The causes of drug abuse among teenagers are due to internal factors and external factors. Internal factors, namely factors that come from a person, where the internal factors themselves consist of personality factors, family factors and economic factors. While external factors, namely factors that come from outside a person or teenager that affect the occurrence of drug abuse. External factors themselves consist of social factors and environmental factors. The objectives to be achieved from this service activity are to provide basic knowledge about the prevention of drug abuse practices among adolescents, especially in Pekanbaru City and provide an explanation of how dangerous drug abuse is for health and the legal sanctions that will be received. The method used in this service consists of three stages, namely the Preparation Stage, Implementation Stage and Evaluation Stage, while the conclusions resulting from this activity are that the partner community who at first before the counseling activities were carried out did not know in detail about the impact caused by drug abuse and the legal sanctions that would be received, after participating in the counseling, the partner community became aware and understood that the impact caused by drug abuse is very extraordinary and the threat of punishment that will be received due to drug abuse is also quite severe, so that the partner community feels that they must be more vigilant so that drug abuse does not occur, especially in the SMK Perbankan Riau
Keywords: Penyalahgunaan; Narkoba; Remaja